PERAN PROJECT MANAGER DAN ACCOUNT EXECUTIVE PADA KAMPANYE “TERBUKA UNTUK SEMUA, BERGERAK BERSAMA WARGA #KULIKDIPORTALSAMAWA” SEBAGAI UPAYA BRAND COMMUNICATION UNTUK MENINGKATKAN BRAND AWARENESS SERTA USER PORTAL SEMARANG SATU DATA DAN SAMAWA (SEMUA DATA UNTUK WARGA) - Zarathustra Zarathustra; Muchamad Yuliyanto (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
The campaign “Terbuka untuk Semua, Bergerak Bersama Warga #KulikdiPortalSAMAWA” aimed to increase awareness and service usage of Portal Semarang Satu Data and SAMAWA. It applied an IMC strategy through events, direct marketing, public relations, and digital campaigns on Instagram @samawa.smg, involving Project Manager and Account Executive roles. Results showed awareness increased by 30.8% (Portal Semarang Satu Data) and 62.7% (SAMAWA), and increase Instagram reach to 10,282 with increase Instagram reach to 10,282with 127,242 visits and 19 service requests, indicating improved public awareness and utilization.